EDUCATIONAL INSTITUTION PREPAREDNESS IN DEALING WITH MOBBING SITUATIONS BETWEEN PUPILS - Jēgere, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Most people spend a significant part of their day at the workplace doing their job, so it is very important that no side-effects hinder the successful and efficient performance of their duties and the employee feels comfortable. In order to prevent mobbing situations at an early stage or not to be formed at all, adults need to critically evaluate the smallest changes in pupils' relationships, and moreover want to notice them in order to see the root in the development of mobing. The theoretical basis of this research consists of the findings of authors such as D.Olweus, H. Leymann, Sperry L., G.P. Elliot and other. Provided insight into the definition of mobing, the causes of the mobing and the most common features, as well as the possible consequences of prolonged mobing. An empirical study is being carried out to find out if there are signs of mobility in the institution and how the management and educators of the institution respond to them, as well as the development of proposals for early detection and prevention of mobbing in its early stages. Within the framework of the research, an interview with the head of the institution was carried out, the teachers participated in the questionnaire and the focus group interview, but the students participated in two surveys. During the empirical research it confirmed that there are signs of mobbing in the institution among the pupils, but the teachers' actions in solving these situations are not always effective because of the lack of necessary knowledge about mobing as a complex problem in the education system. Suggestions for improving the situation are provided.